Magnetic Vibration in Induction Motor Caused by Supply Voltage Distortion - Artem Ermolaev; Vladimir Erofeev; Aleksandr Plekhov; Dmitry Titov (Energies, 2022)
This article discusses magnetic vibrations in squirrel-cage induction motor stators and provides a mathematical description of the process of their excitation. A model of a 30 kW squirrel-cage induction motor was developed in finite element software. This model considers the motor geometry, material properties and stator winding. The electromagnetic and mechanical processes in the motor during the rotation of the rotor were considered. In the course of this study, currents of various harmonic compositions and amplitudes were applied to the motor windings, which caused magnetic noise, vibration and pulsations of the electromagnetic torque. Magnetic noises, vibrations and pulsations of the electromagnetic torque were investigated in the case of imbalance and harmonic distortions of the supply voltage.